Shelf life and quality assessment of pasteurised red dragon fruit (Hylocereus polyrhizus L.) purée: comparative study of high-pressure and thermal processing - Ismail, N. H. S.; Nawawi, N.I.M.; Ijod, G.; Anzian, A.; Ismail-Fitry, M. R.; Ahmad, N. H.; Adzahan, N. M.; M. Azman, E. (Universiti Putra Malaysia, 2024)
Red dragon fruit (RDF; Hylocereus polyrhizus L.) contains various polyphenols with potent antioxidant properties. Purée extracted from RDF has a vibrant red hue, making it a valuable natural food colouring agent suitable for a wide range of culinary applications. To preserve this valuable purée, non-thermal pasteurisation methods, such as high-pressure processing (HPP), have emerged as an alternative to thermal pasteurisation (TP), as they do not impart the adverse effects associated with heat treatment. Therefore, the primary objective of the present work was to compare the impact of HPP and TP on several key attributes of RDF purée during 60-d storage. These attributes included the total betacyanin content (TBC), total phenolic content, total flavonoid content (TFC), antioxidant activities, enzyme activities, microbial growth, and colour stability. The RDF purée samples were divided into three groups: TP-treated (65°C/20 min), HPP-treated (350 MPa/5 min), and an untreated control group. All samples were stored at a controlled temperature of 4 ± 1°C, and analysed at 15-d intervals. Results revealed that preservation method, storage duration, and their interactions, significantly influenced the various parameters studied in RDF purée. Notably, HPP demonstrated superior efficacy in extending the shelf life of RDF purée well beyond 60 d, outperforming both TP and Control. Specifically, TP was proven effective in maintaining the phenolic content, antioxidant activities, and colour stability of the purée. On the other hand, HPP was particularly efficient in suppressing microbial growth and reducing enzyme activities in RDF purée. The findings can potentially transform the way RDF purée is preserved and utilised in the food industry, benefiting both producers and consumers, and contributing to more sustainable and health-conscious food practices.